Pelaksanaan Pembelajaran Daring Seni Budaya Di Kelas VII SMP Negeri 7 Padang - Tyas Widyanti; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2020)
This study discusses the Implementation of Online Learning in SMP Negeri 7 Padang. This research is a qualitative research and it uses the descriptive analytic approach which tends to use theoretical basis analysis used to guide the focus to be in accordance with the facts in the field. The research data were collected through interviews done to informants. Based on the results of the research implemented in two meetings, the author concludes that the implementation of online learning of Cultural Arts in music ensemble material to class VII.1 SMP Negeri 7 Padang is the use of WhatsApp Group media recommended by the assistant principle of Curriculum of SMP Negeri 7 Padang to deal with online learning so that learning activities still can be constructed even in a remote condition. The planning of online learning of music ensemble material is not optimal because the teachers do not create lesson plans specifically for the online learning process. The implementation of online learning in Cultural Arts in class VII is in accordance with the lesson plans implemented during face-to-face learning in the classroom. The online learning of Cultural Arts of the ensemble music material continues to run smoothly despite the simple learning. The learning outcomes of Cultural Arts of music ensemble of class VII are less than optimal because the learning activities are constructed without paying attention to the standards related to the preparation of online learning materials.